2020
DOI: 10.1111/cp.12206
|View full text |Cite
|
Sign up to set email alerts
|

Burnout in psychological therapists: A cross‐sectional study investigating the role of supervisory relationship quality

Abstract: Background Burnout is a growing problem in mental health‐care professionals. Clinical supervision is a mandated part of all psychological therapeutic practice but no previous study has explored whether higher quality supervision is associated with lower burnout in qualified psychological therapists. Aims The study aimed to investigate whether the quality of the supervisory relationship was associated with two facets of burnout, exhaustion and disengagement, in a group of psychological therapists once work dema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…The efficacy of mHealth for supervisions to reduce stress and burnout in clinical staff could not be reviewed due to the dearth in research. Previous research has evidenced the propensity of clinical supervisions to reduce stress and burnout (Oates, 2018; Jarden et al , 2019; Johnson et al , 2020); however, no empirical research could be found regarding the use of mHealth in this process. Due to the exponential increase drove by the COVID-19 pandemic, further research would benefit from utilising mHealth apps during the course of clinical supervision to provide the option to record and reflect upon the pejorative aspects of clinical staff employment, so that causal factors of stress and burnout may be identified and rectified, prior to onset.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of mHealth for supervisions to reduce stress and burnout in clinical staff could not be reviewed due to the dearth in research. Previous research has evidenced the propensity of clinical supervisions to reduce stress and burnout (Oates, 2018; Jarden et al , 2019; Johnson et al , 2020); however, no empirical research could be found regarding the use of mHealth in this process. Due to the exponential increase drove by the COVID-19 pandemic, further research would benefit from utilising mHealth apps during the course of clinical supervision to provide the option to record and reflect upon the pejorative aspects of clinical staff employment, so that causal factors of stress and burnout may be identified and rectified, prior to onset.…”
Section: Discussionmentioning
confidence: 99%
“…Other research has suggested that regular clinical supervisions may allow clinical staff to debrief and make sense of workplace complexities (Jarden et al , 2019; Brennan, 2017), subsequently, improving mental well-being. Regular, high quality supervisions have been found to be efficacious to monitor and reduce stress and burnout in clinical settings (Love et al , 2017; Johnson et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…High levels of clinical supervision were viewed favourably by counsellors and were linked with staff well‐being and high retention rates. Despite conflicting findings (Watkins, 2020), the importance of formal and informal supervision in supporting staff and as a protective factor against secondary traumatic stress has been highlighted in the AOD and psychotherapy literature (Bride & Kintzle, 2011; Ewer et al., 2015; Johnson et al., 2020; Laschober et al., 2013). In addition, counsellor autonomy regarding intervention approaches and in selecting professional development opportunities has been shown to increase job satisfaction (Gallon et al., 2003; Knudsen et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence; however, that supervision may be a meaningful protective factor against counsellor burnout and STS (e.g., Hiebler-Ragger et al, 2021 ; Quinn et al, 2019 ). The strength of this relationship is less clear (Johnson et al, 2020 ). For example, Hiebler‐Ragger et al (2021) found that supervisees’ perceptions of a strong supervisory relationship were related to decreased burnout.…”
Section: Prelicensed Counsellors Clinical Supervision and Tismentioning
confidence: 99%